What catalyses mobile apps usage intention: an empirical analysis. Issue 7 (10th August 2015) - Hew, Jun-Jie; Lee, Voon-Hsien; Ooi, Keng-Boon; Wei, June
Abstract : Purpose: – Considering the lack of understanding of the mobile applications (mobile apps) market and low usage rates among Malaysians, Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) was adapted to investigate the determinants of consumer behavioural intention (BI) to use mobile apps. Design/methodology/approach: – A total of 288 sample data was collected and analysed using partial least square equation modelling (PLS-SEM) method. Findings: – All of UTAUT2 constructs (i.e. performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, and habit), except for price value and social influence, significantly relate with BI to use mobile applications. Habit was reported to have the strongest influence. Gender and educational level were found to be insignificant moderators. Practical implications: – Mobile application developers could have better understanding on users' needs and intention, based on the findings. Originality/value: – In order to shed light on current problems, and there is a dearth in relevant studies which could resolve the issue, this paper contributes the necessary knowledge on mobile apps acceptance to developers. Educational level was added into UTAUT2 as a moderator in addition to gender.